Compliance Among Nurses Using Personal Protective Equipment in The Hospital: Literature Study - Julianto, Rahmad; Desiana, Desiana; Hanum, Lathifah; Cipta, Hendra (Poltekkes Kemenkes Aceh, 2025)
Background: Hospital-acquired nosocomial infections, which cause more than 100,000 patient deaths each year, are often associated with poor nurse compliance with prevention guidelines, including the use of Personal Protective Equipment (PPE). Compliance with PPE effectively reduces the risk of infection, but several studies have shown low levels of nurse compliance, associated with unfavorable work environments, high workloads, and lack of knowledge and competence. Following the Covid-19 pandemic, compliance with PPE has become increasingly important in preventing the spread of infectious diseases. Purpose: To determine the factors related to the level of nurse compliance in using PPE. Methods: This study uses a literature study method to explore factors related to the level of nurses' compliance in using PPE. Data were taken from articles published from January 2023 to January 2024 through the Pubmed National Library of Medicine database. Article searches were limited by the criteria of articles having full text, in English, and keywords used in the search including compliance, nurses, personal protective equipment (PPE), and nosocomial infections. Results: Research shows that nurses' knowledge, attitudes, behaviors, education, training, and motivation play a significant role in increasing awareness of PPE use. In addition, adequate provision of PPE, supporting facilities, safety culture, hospital organizational commitment, and government regulations also determine compliance. Conclusion: Although the availability of PPE facilities is a major contribution to prevention, nurse preparedness is needed to reduce disease transmission and ensure that the health care system continues to function during times of crisis, especially during the spread of infectious diseases.